Television and anthropology: an unhappy marriage? - Banks, M (Routledge, 1994)
This paper surveys ethnographic film as it has been presented over the years on British television, particularly in the Disappearing World series. A detailed criticism leads to the conclusion that anthropologists should not place too much faith in the kind of films that are presented for the general public on television. The involvement of anthropologists in these productions has often amounted to a less-than-happy marriage.